Methodology in Accounting Theory. - Buckley, John W.; Kircher, Paul; Mathews, Russell L. (The Accounting Review, 1968)
Abstract The article focuses on the problems of methodology in accounting theory and principle. If a general methodology in accounting could be agreed upon, theories developed within this framework would stand a better chance of gaining widespread approval. As it is now, both the ends and the means are constantly in dispute. In accounting, there has been a long-standing belief that accounting is an art which does not lend itself to formalization. This attitude is being challenged increasingly. The effort towards formalization must face the issue of improving methodology, otherwise researchers in the field may be working at cross-purposes. Here the author discusses the difficulties which arise when accounting theory is developed without sufficient attention to the conceptual framework, and shows how theory formulation in accounting may progress by adherence to a more formal general methodology. He remarks that lack of methodology in accounting theory in the past has resulted in poor definition of terms.